Comprehensive annotations of the mutational spectra of SARS‐CoV‐2 spike protein: a fast and accurate pipeline. Issue 3 (6th October 2020) - Rahman, Mohammad Shaminur; Islam, Mohammad Rafiul; Hoque, Mohammad Nazmul; Alam, Abu Sayed Mohammad Rubayet Ul; Akther, Masuda; Puspo, Joynob Akter; Akter, Salma; Anwar, Azraf; Sultana, Munawar; Hossain, Mohammad Anwar
Abstract: Infecting millions of people, the SARS‐CoV‐2 is evolving at an unprecedented rate, demanding advanced and specified analytic pipeline to capture the mutational spectra. In order to explore mutations and deletions in the spike (S) protein — the most‐discussed protein of SARS‐CoV‐2 — we comprehensively analyzed 35, 750 complete S protein‐coding sequences through a custom Python‐based pipeline. This GISAID‐collected dataset of until 24 June 2020 covered six continents and five major climate zones. We identified 27, 801 (77.77% sequences) mutated strains compared to reference Wuhan‐Hu‐1 wherein 84.40% of these strains mutated by only a single amino acid (aa). An outlier strain (EPI_ISL_463893) from Bosnia and Herzegovina possessed six aa substitutions. We also identified 11 residues with high aa mutation frequency, and each contains four types of aa variations. The infamous D614G variant has spread worldwide with ever‐rising dominance and across regions with different climatic conditions alongside L5F and D936Y mutants, which have been documented throughout all regions and climate zones, respectively. We also found 988 unique aa substitutions spanned across 660 residues, which differed significantly among different continents ( p  = .003) and climatic zones ( p  = .021) as inferred with the Kruskal–Wallis test. Besides, 17 in‐frame deletions at four sites adjacent to receptor‐binding‐domain were determined that may have a possible impact on attenuation. This study provides a fast and accurate pipeline for identifying mutations and deletions from the large dataset for coding and also non‐coding sequences as evidenced by the representative analysis on existing S protein data. By using separate multi‐sequence alignment, removing ambiguous sequences and in‐frame stop codons, and utilizing pairwise alignment, this method can derive both synonymous and non‐synonymous mutations (strain_ID reference aa:mutation position:strain aa). We suggest that the pipeline will aid in the evolutionary surveillance of any SARS‐CoV‐2 encoded proteins and will prove to be crucial in tracking the ever‐increasing variation of many other divergent RNA viruses in the future. The code is available at https://github.com/SShaminur/Mutation-Analysis .